Development and validation of the methods of captopril spectrophotometric determination in blood by the reaction with the Ellman reagent - Klimenko, L. Yu.; Showkova, Z. V.; Mykytenko, O. Ye.; Kaplaushenko, A. G.; Шовкова, З. В.; Микитенко, О. Є.; Клименко, Л. Ю.; Шовковая, З. В.; Микитенко, Е. Е.; Каплаушенко, Андрій Григорович (Запорізький державний медичний університет, 2014)
Aim. To rationalize quantitative determinations in forensic and toxicological analysis, the possibility to use the method of standard for analytes quantitative determination in biological fluids has been studied. Methods and results. The series of spectrophotometric methods of captopril quantitative determination in blood based on reaction with the Ellman reagent has been developed using amphiphylic solvents (isopropanol, acetonitrile, methanol) in condition of aqueous phase saturation by ammonium sulphate. Validation of the developed methods in the variant of the method of standard has been carried out, conformity of the obtained values of validation parameters to the acceptability criteria has been shown. Conclusion. It has been set that acetonitrile application in the acid medium (рН=2) is optimal. З метою раціоналізації здійснення кількісних визначень у судово-токсикологічному аналізі вивчили можливість використання методу стандарту для кількісного визначення аналітів у біологічних рідинах. Розробили серію спектрофотометричних методик кількісного визначення каптоприлу у крові, що ґрунтуються на реакції з реактивом Еллмана, з використанням амфіфільних розчинників (ізопропанолу, ацетонітрилу, метанолу) в умовах насичення водної фази амонію сульфатом. Виконали валідацію методик у варіанті методу стандарту, показали відповідність значень валідаційних параметрів, які отримали, до критеріїв прийнятності. Встановили, що оптимальним є використання ацетонітрилу в кислому середовищі (рН = 2). С целью рационализации проведения количественных определений в судебно-токсикологическом анализе изучена возможность использования метода стандарта в ходе количественного определения аналитов в биологических жидкостях. Разработана серия спектрофотометрических методик количественного определения каптоприла в крови, основанных на реакции с реактивом Эллмана, с использованием амфифильных растворителей (изопропанола, ацетонитрила, метанола) в условиях насыщения водной фазы аммония сульфатом. Проведена валидация разработанных методик в варианте метода стандарта, показано соответствие полученных значений валидационных параметров критериям приемлемости. Установлено, что оптимально использование ацетонитрила в кислой среде (рН=2).
Розробка та валідація методик спектрофотометричного визначення каптоприлу у крові за реакцією з реактивом Еллмана
Разработка и валидация методик спектрофотометрического определения каптоприла в крови по реакции с реактивом Эллмана
Keywords: validation studies; analitical chemistry techniques; captopril; ellman’s reagent; spectrophotometry; валідація; біоаналітичні методики; каптоприл; реактив Еллмана; спектрофотометрія; валидация; биоаналитические методики; каптоприл; реактив Эллмана; спектрофотометрия